Trace Element Geochemistry of Volcanogenic Massive Sulfide Deposits in Archean Greenstone Belts: Implications for Metal Endowment and Geodynamic Settings - Penner, Ryley (Université d'Ottawa / University of Ottawa, 2023)
The Neoarchean greenstone belts of the Canadian Superior Province host world-class Au and base metal (Cu-Zn-Pb) massive sulfide deposits with distinct geological features, including a wide range of different host rocks and crustal settings. The range of settings is reflected in the trace metal signatures of their ores. This study examines the trace element geochemistry of pyrite from 55 different Archean volcanogenic massive sulfide (VMS) deposits in Canada to test the relationship to their host rocks, the deposit sizes and their grades. The database includes 258 samples of pyrite from 47 deposits in the Abitibi Greenstone Belt (AGB), together with 30 samples from 8 deposits in the Western Superior (Sturgeon Lake, Uchi, Benny, and Manitouwadge belts) and 45 samples from 6 deposits in the Slave Province (Hackett River, Amooga Booga, and High Lake belts). We used statistical methods to characterize the trace element geochemistry of pyrite in grab samples from the deposits, as well as larger samples representing many thousand of tonnes of ore from monthly concentrates. The study focused on pyrite mineral separates comparing samples from different deposits and different ore types within individual deposits. The analysis shows the trace element geochemistry of pyrite is a useful fingerprint of the different mineralizing systems, with trace element enrichments and depletions reflecting different source rocks, inferred temperatures of ore formation, and the scales of the hydrothermal systems. A comparison of the Abitibi samples to other deposits in the Superior Province shows distinct trace element signatures between primitive and more evolved crustal settings of different age. Similar results are found among 102 samples of pyrite from 30 deposits in Proterozoic and Phanerozoic belts across Canada. District-scale variations in pyrite chemistry mainly reflect host rock and correlate different bulk Cu/(Cu+Zn) grade ratios of the deposits. Pyrite samples from Cu-rich deposits are enriched in Cu, Bi, Co, Ni, Se, Te and Mo; whereas pyrite samples from Zn-rich deposits are enriched in Pb, Ag, Cd, In, Ga, Sn, As, Sb, Hg and Tl. The same patterns are observed in Cu-rich versus Zn-rich zones of individual deposits. Statistical analyses reveal pyrite samples from VMS deposits in the AGB that are associated with primitive mafic-ultramafic tholeiitic rocks (e.g., Potter-Doal and Genex from Timmins, and East Sullivan and Dunraine from Val d'Or camps) are enriched in Cu (>5000 ppm), Co (>1500 ppm), Se (>4000 ppm), and Ni (>250 ppm), whereas pyrite from deposits associated with tholeiitic to calc-alkaline felsic rocks (e.g., Abcourt-Barvue from the Amos-Barraute camp) are commonly enriched in Pb, Ag, Au, Cd, In, Sn, As, Sb, Hg, Tl (10s to 100s of ppm). These variations closely match primary trace element abundances in unaltered volcanic rocks compiled from over 4000 high-quality analyses of samples from the Superior Province. Whole-rock data for rhyolite confirm high concentrations of Pb, Ag, Bi, Te, Cd, In, Ga, Sn, Hg, and Tl compared to basalt and komatiite, which have higher Cu, Co, Ni, and Se. The variation in trace element concentrations in pyrite is remarkably consistent for different deposits. We note that randomly sampled pyrite from almost any part of a deposit with a bulk enrichment in a particular element shows notable enrichment in that element compared to pyrite from other deposits. Pyrite from a deposit with a bulk enrichment in Te, for example (Quemont in the Noranda camp), will almost certainly contain more Te than pyrite from other Te-poor deposits. We test this observation among 47 deposits for 15 different elements. Pyrite samples from Au-rich VMS deposits (e.g., Horne, Quemont, Bousquet #2, and Dumagami) have anomalous Au (>6 ppm) and Te (>70 ppm). Co-enrichment in other elements such as Bi, Se, In and Sn may reflect a common felsic magmatic source. Other trace element enrichments appear to reflect the scale of the hydrothermal system (e.g., depth and extent of leaching). For example, pyrite samples from several large-tonnage deposits (Kidd Creek, Horne #5 Zone, and Geco) have high Sn concentrations (from 450 to 15000 ppm) possibly reflecting the large volumes of felsic rock from which the Sn was extracted. In other deposits, co-enrichment of Sn with Bi (>100 ppm) and In (>10 ppm) suggest a magmatic contribution to the ore fluids Principal Components Analysis (PCA) combined with hierarchal clustering confirms systematic trace element variability in pyrite from deposits with different host rocks and bulk Cu/(Cu+Zn) ratios. However, pyrite from deposits in different terranes seems to record major differences in the crustal compositions of those terranes. For example, pyrite samples from bimodal-felsic deposits show the same trace element signatures (i.e., enrichments in Ag, As, Sb, and Hg) in the AGB and in the Western Superior. In contrast, pyrite samples from deposits in the Slave craton tend to show a distinct enrichment in Pb, U and Th that may be related to the more mature and thicker crust in the Slave compared to the AGB. Other deposit types (magmatic Cu vein deposits, orogenic Au deposits) also show dramatically different pyrite compositions. Pyrite concentrates from magmatic Cu vein deposits in Chibougamau are enriched in Cu, Co, Ni, Te, As, Sb compared to VMS in the AGB, and samples from orogenic Au deposits in Timmins and Val d'Or are enriched in Au and Mo and depleted in Pb, Bi, As, and Sb compared to VMS. These differences highlight the potential application of the trace element signatures of pyrite during exploration for different deposit types in the same region. Trace element signatures of pyrite in grab samples compared favourably to much larger bulk samples from the same deposits (e.g., monthly concentrates and mine tailings) giving some confidence that the much smaller samples can provide a reliable first-order fingerprint of the deposits as a whole. LA-ICP-MS analyses of individual pyrite grains also agreed well with bulk analyses of pyrite over a wide range of trace element concentrations (10s to 100s of ppm).
Keywords: Geochemistry; Economic Geology; Ore Deposits; Trace Metals